A comparative analysis of Islamic unit trust portfolio using value at risk methodologies / Farah Azaliney Mohd Amin ... [et al.] - Mohd Amin, Farah Azaliney; Ghazali, Nur Qamarina; Zainalbidin, Nursahira; Kamarudin, Nur Najwa Alia (Universiti Teknologi MARA, 2020)
Islamic unit trust is a sunrise industry in the Malaysian capital market over the last decades to fulfill the demand from its Muslim investors. Muslim investors are only willing to invest their capital if the investment does not conflict with their religious beliefs, namely Islam. Previously, most of the studies focused to evaluate the performance of unit trust funds relative to the market as a whole. Meanwhile, it is also important for investors to accurately measure their downside risk because it is closely related to their future losses. Thus, Value at Risk (VaR) concept was introduced to calculate monthly risk for an Islamic unit trust portfolio using the three standard approaches which are Delta Normal, Historical Simulation and Monte Carlo Simulation. Results show that Monte Carlo Simulation is the best method to quantify risk exposure as the average Mean Absolute Percentage Error (MAPE) is the lowest compared to the other two methods. The findings also highlight the importance of embedding risk into investment analyses and provide insights to investors who are considering Shariah-compliant equity funds as a potential income-generating instrument. Therefore, financial consultants or fund managers can make informed decisions in setting up a well-diversified unit trust fund’s portfolio for their Muslim investors by applying the concept of VaR and its methodologies.